Adoption of direct oral anticoagulants for stroke prevention in atrial fibrillation. Issue 7 (July 2016) - Baker, D.; Wilsmore, B.; Narasimhan, S.
Abstract : Background: Direct oral anticoagulants (DOAC) are being increasingly utilised for stroke prevention in atrial fibrillation (AF) and atrial flutter. Aims: To analyse the adoption and application of these drugs in a regional hospital inpatient cohort and compare with national prescribing data. Methods: Digital medical records identified prescribed anticoagulants for patients admitted with AF and atrial flutter during 2013–2014. Analysis of patient demographics and stroke risk identified trends in prescribing DOAC versus warfarin. For broader comparison, data from the Pharmaceuticals Benefits Scheme were sourced to determine the nation‐wide adoption of DOAC. Result: Of the 615 patients identified, 505 (255 in 2013, 250 in 2014) had sufficient records to include in the study. From 2013 to 2014, DOAC prescriptions increased from 9 to 28% ( P  < 0.001), warfarin and aspirin remained comparatively stable (38–34%, 22–20%), and those prescribed no medication declined (17–8%, P  < 0.001). DOAC were prescribed to patients with lower CHA2 DS2 VASc scores than warfarin (3.6 vs 4.4; P  = 0.005), lower HAS‐BLED scores (1.7 vs 2.3; P  < 0.01), higher glomerular filtration rates; 70 vs 63 ml/min; P  = 0.002) and younger age (74 vs 77 years; P  = 0.006). Nationally, warfarin prescriptions are higher in total numbers but increasing at a slower rate than DOAC, which increased 10‐fold (101 158 in 2013, 1 095 985 in 2014). Conclusion: DOAC prescribing grew rapidly from 2013 to 2014, regionally and nationally. Warfarin prescriptions have remained stable, indicating that more patients are being appropriately anticoagulated for AF who previously were not. DOAC were found to be prescribed to patients with lower CHA2 DS2 VASc and HAS‐BLED scores, younger age and higher glomerular filtration rates. Aspirin therapy remains over utilised in AF.